Adapting, updating and translating the Social Functioning Scale to assess social, recreational and independent functioning among youth with psychosis in diverse sociocultural contexts. Issue 7 (7th November 2021) - Pawliuk, Nicole; Malla, Ashok; Mohan, Greeshma; Taksal, Aarati; Pope, Megan A.; Birchwood, Maximillian; Mangala, Ramamurti; Ramachandran, Padmavati; Loohuis, Heleen; Schmitz, Norbert; Joober, Ridha; Shah, Jai; et al.
Abstract: Aim: To compare social, recreational and independent functioning among persons with psychosis across two geo‐cultural contexts, we adapted the well‐established Social Functioning Scale (SFS) and translated it into French and Tamil. We present the development and psychometric testing of this adaptation, the SFS‐Early Intervention. Methods: Sixteen items were added to reflect contemporary youth activities (e.g., online games) and 31 items adapted to enhance applicability and/or include context‐specific examples (e.g., 'church activity' replaced with 'religious/spiritual activity'). Psychometric properties and participant feedback were evaluated. Results: Test–retest reliability (ICCs) ranged from 0.813 to 0.964. Internal consistency (Cronbach's α ) ranged from .749 to .936 across sites and languages. Correlations with original subscales were high. The scale was rated easy to complete and understand. Conclusions: The SFS‐Early Intervention is a promising patient‐reported measure of social, recreational and independent functioning. Our approach shows that conceptually sound existing measures are adaptable to different times and contexts.